2001
DOI: 10.1002/jmv.2077
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of an influenza B virus isolated from a patient with encephalopathy in Japan*

Abstract: An influenza B virus, B/Saga/S172/99 (SAG99), was isolated from the nasopharynx of a patient with encephalopathy/encephalitis in Japan in 1999. To clarify the molecular characteristics of this virus, detailed analysis of the gene segments coding for the hemagglutinin (HA), neuraminidase (NA), nucleoprotein (NP), matrix protein (M) and non-structural protein (NS) was undertaken. All five genes of SAG99 showed high nucleotide and predicted amino acid similarities with those of recent non-encephalopathic strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…the following two seasons, Yamagata/222/2002, Yamagata/115/2003, Yamagata/1246, and Yamagata/ 1311, were also determined here. Phylogenetic trees of individual genes were constructed using these sequences in addition to the previous reported sequences [Yamashita et al, 1988;Kanegae et al, 1990;Rota et al, 1990;Nerome et al, 1998;Lindstrom et al, 1999;McCullers et al, 1999;Hiromoto et al, 2000;Shiraishi et al, 2001;Shaw et al, 2002]. The genome composition of the newly studied isolates is summarized in Table I. HA1 and NS gene trees.…”
Section: Isolation Of Influenza B Virusesmentioning
confidence: 99%
“…the following two seasons, Yamagata/222/2002, Yamagata/115/2003, Yamagata/1246, and Yamagata/ 1311, were also determined here. Phylogenetic trees of individual genes were constructed using these sequences in addition to the previous reported sequences [Yamashita et al, 1988;Kanegae et al, 1990;Rota et al, 1990;Nerome et al, 1998;Lindstrom et al, 1999;McCullers et al, 1999;Hiromoto et al, 2000;Shiraishi et al, 2001;Shaw et al, 2002]. The genome composition of the newly studied isolates is summarized in Table I. HA1 and NS gene trees.…”
Section: Isolation Of Influenza B Virusesmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21] Some studies in Japan have provided direct evidence of the influenza virus genome in cerebrospinal fluid. [22][23][24] However, recent studies indicate that several cytokines might mediate the disease and a high plasma concentration of interleukin-6 could be an indicator of progression to encephalopathy, thus the direct viral invasion might not be responsible for all of the symptoms. 25,26 The study of Kamimura et al reported that in a studied group most fatal cases of influenza-associated acute encephalopathy/encephalitis occurred in the first influenza infection, and that these patients had not been immunized.…”
mentioning
confidence: 99%
“…Influenza‐related acute encephalopathy/encephalitis is rarely seen except in cases of Reye syndrome, and epidemics have rarely been reported in other countries 12−21 . Some studies in Japan have provided direct evidence of the influenza virus genome in cerebrospinal fluid 22−24 . However, recent studies indicate that several cytokines might mediate the disease and a high plasma concentration of interleukin‐6 could be an indicator of progression to encephalopathy, thus the direct viral invasion might not be responsible for all of the symptoms 25,26 .…”
mentioning
confidence: 99%
“…In the English-language literature, 21 cases of IBAE have been reported [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Eight cases were excluded from this analysis: 4 were reported in articles that contained insufficient information for analysis [15][16][17][18], 3 were reported in studies that failed to provide adequate serologic or cell culture-based evidence of influenza B virus infection [6,19], and one case may have been Reye syndrome [20].…”
Section: Resultsmentioning
confidence: 98%